The implementation of narrative counseling for reducing final-year students' anxiety - Nissa, Fadlun; Primana, Linda (Universitas Islam Negeri Raden Intan Lampung, 2023)
Final-year university students face the pressure of completing their theses, planning their careers, and preparing for life after graduation, leading to uncontrollable anxiety. This study aims to examine the effectiveness of applying narrative counseling in reducing anxiety in final-year students. Employing a single-subject design, the research focuses on students experiencing anxiety related to the demands of their final year. Data were collected using Beck’s Anxiety Inventory to measure changes in anxiety levels before and after the counseling process. Counseling effectiveness was also assessed qualitatively based on goal achievement, the subject's reflection on the four counseling stages, and the implementation of anxiety regulation strategies. The study results indicate a reduction in anxiety levels, supported by both Beck’s Anxiety Inventory scores and qualitative data obtained during the narrative counseling process.